Comparison of lactate and ventilatory threshold to maximal oxygen consumption: A meta-analysis - Wyatt, F. B.; Tran, Z. V.; Jackson, C. G.; Brustad, R. J.; Banchero, N. (Medicine & Science in Sports & Exercise, 1996)
Sixty-one studies were reviewed and subjected to a meta-analysis to determine associations between lactate (LT) and ventilatory (VT) inflection points and maximal oxygen consumption. The following were concluded. 1. Maximal oxygen consumption is not a good predictor of LT or VT. 2. LT and VT are similar. 3. Fitness level changes can alter the LT. 4. VT differs between men and women. 5. The apparatus used for testing can influence the VT. It was concluded that LT measures can be considered for determining lactate inflection point. Implication. LT and VT are similar and may be used interchangeably in field tests and applications. (see also: http://apt.allenpress.com/aptonline/?request=get-abstract&issn=1064-8011&volume=013&issue=01&page=0067, The Journal of Strength & Conditioning Research: Vol. 13, No. 1, pp. 67-71)